Short-term effects of air pollution on daily asthma-related emergency department visits in an industrial city. (19th March 2020) - AlBalawi, Salem M; Namdeo, Anil; Hodgson, Susan; Pless-Mulloli, Tanja; McNally, Richard J Q
Abstract: Background: Epidemiological studies from Europe and North America have provided evidence that exposure to air pollution can aggravate symptoms in asthmatic patients. Methods: Daily number of AEDv, air pollution levels (PM10, PM2.5, SO2, NO2 and CO) and meteorological variables was obtained from Jubail Industrial City, Saudi Arabia, for the period of 2007–11. Data were analyzed using a time-series approach. Relative risks (RRs) were estimated using Poisson regression. Results: The associations between AEDv and PM10, PM2.5, SO2 and NO2 remained positive and statistically significant after mutual adjustment in the multi-pollutant model. The RR of AEDv increased by 5.4, 4.4, 3.4 and 2.2% per an inter-quartile range increase in SO2 (2.0 ppb), PM2.5 (36 μg/m 3 ), NO2 (7.6 ppb) and PM10 (140 μg/m 3 ), respectively. No significant associations between AEDv and CO were found. Conclusions: Current levels of ambient air pollution are associated with AEDv in this industrial setting in the Middle East. Greater awareness of environmental health protection and the implementation of effective measures to improve the quality of air in such settings would be beneficial to public health.